Analisis Perhitungan Harga Pokok Produksi - M. Aldian Fikri; Syaharman Syaharman (Universitas Islam Islam Sumatera Utara, 2022)
The purpose of this research is to determine the accuracy of the calculation of Cost of Goods Manufactured by CV. Boga Amanda according to the full costing method. The data analysis technique used in this research is using descriptive analysis techniques. The result of this research is to see the comparison of The Cost of Goods Sold (COGS) with the company method and the full costing method. The results of both comparisons are COGS using the full costing method is greater than COGS using the company method. The value of the cost of goods manufactured using the full costing method is Rp. 2,990,835,000 while the value of the cost of goods manufacured using the company method is Rp. 2,986,983,000 so that there is a difference in calculation of Rp. 2,990,835,000 - Rp. 2,986,983,000 = Rp. 3,852,000. The value on the basis of the cost of goods manufactured using the full costing method is Rp. 43,561 while the cost of goods manufactured using the company method is Rp. 43,505 so that the difference in the calculation of the cost of goods manufactured is Rp. 43,561 - Rp. 43,505 = Rp. 56. The conclusion of this research is the calculation of the selling price using the full costing method has a higher value because the cost of manufactured is higher while the calculation of the selling price using the company is lower because the cost of manufactured is low. The company should make notes in the production process and the costs are classified based on the main functions of the company's activities to facilitate the calculation of the cost of goods manufactured.